Using moodle analytics for continuous e-assessment in a financial mathematics course at Polytechnic of Porto - Lopes, Ana Paula (2019)
The relevance of electronic learning, commonly called e-learning, has been growing exponentially in the last decade. Virtual learning environments (VLEs) disclosed new paths for interactions and motivation promotion, offering basic learning analytics functions and are becoming progressively popular. Moodle (acronym for Modular Object Oriented Dynamic Learning Environment) is one of the most used VLEs, it is a free learning management system distributed as Open Source. The VLE Moodle gives professors access to an “endless” use and performance database like the number of downloads for each resource, participation of students in courses, statistics of performed quizzes, among others. The data stored by Moodle offers a good and handy source for learning analytics. One popular definition, from the First International Conference on Learning Analytics and Knowledge in 2011, states that “Learning Analytics is the measurement, collection, analysis and reporting of data about students and their contexts, for purposes of understanding and optimizing learning and the environments in which it occurs”. Thus, using appropriate learning analytics methods and techniques, it would be helpful to analyze what particular learning activities or tools were practically used by students in Moodle, and to what extent. Considering the importance of the student engagement and the benefits of continuous assessment in higher education, as well as the impact of information and communications technology (ICT) on educational processes, it is important to integrate technology into continuous assessment practices. Since student engagement is connected to the quality of the student experience, increasing it is one way of enhancing quality in a higher education institution. In this study, will be demonstrated how the use of several educational resources and a low-stakes continuous weekly e-assessment in Moodle had a positive influence on student engagement in a second year undergraduate Financial Mathematics Course. Students felt that their increased engagement and improved learning was a straight result of this method. Furthermore, this suggests that wisely planned assignments and assessments can be used to increase student engagement and learning, and, as a result, contribute to improving the quality of student experience and success.